The effect of complex training using the intermittent method in developing the special strength ability and achievement of young shot-put player U 20 - Hasaneen, Shaimaa; alshammaa, haydar; Mahdi, Abeer; Hashim, maryam (Journal of Physical Education, 2024)
Complex training, which is of great importance in the development of physical capabilities through change in the motor path and diversity of exercises for the same muscle groups working during the motor performance, which depends on the ability of the muscular and nervous systems in the process of compatibility, and work to apply it in the intermittent training method that works on the continuous change in the degree of difficulty of exercise (intensity of training) coordinated with rest periods and designed to develop the ability of special forces for archers to push weight and achievement, andThe aim of the study is to prepare complex exercises in the intermittent method over a period of 6 weeks (12) training units during the special preparation stage, on a sample of young people under 20 years of age (5) elite athletes effectively push the weight, the study variables measured two variables for maximum strength of the arms and chest, explosive force of the two men, rapid force of the arms and achievement by pushing the weight.Through pre and posttests, the researchers concluded the effectiveness of combined training, which is regulated by intermittent training, in the development and improvement of the special ability of the weightlifting archers (the explosive power of the two men, the maximum strength and the rapid strength of the shoulders and arms) and the exercises have made a clear progress in the achievement of weight propulsion for young people under 20 years.